Use of Transient Absorption Spectroscopy to Probe Unexpected Phenomena in Organic Electronics - Marín-Beloqui, José Manuel (My University, 2024)
Organic photovoltaics have the capability to overcome to their inorganic counterparts due to several reasons like low weight, flexibility and low price. Transient Absorption Spectroscopy (TAS) represents the perfect tool to study this kind of devices. TAS is a pump-probe technique, with two different light sources: one excites the sample whereas the other probes the photogenerated excited states. This way, with TAS, we are able to follow the different processes taking place in organic photovoltaics, from charge photogeneration to the different efficiency loss pathways. In this work two different systems are presented where unexpected behaviour is obtained. In the first case, DRCN5T is studied. DRCN5T is a well extended material used in binary and ternary solar cells as small molecule donor. In our work, how this molecules is able to generate a large number of triplets is demonstrated, despite being able to obtain large efficencies. In addition, the annealing process is shown that largely increases the number of triplets generated in this material. The second family to be studied is a range of NDI materials where some substituents is systematically changed in order to stablish a difference between the orthogonality between the core and the substituent. With the help of TAS, it is shown how the orthogonality is associated with an enhancement in the charge generation for these materials.
Keywords: Espectroscopía; Transient Absorption Spectroscopy; Organic Electronics; Spectroscopy